2007
DOI: 10.1177/152692480701700312
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Living Kidney Donation Experience and Implications for Education

Abstract: Findings indicated that education is the best way to reach living donors and dispell fears. Promoting general health of African Americans may increase their willingness to be a living donor. Altruistic motives are the main motivation for donation, and intervention programs should target groups on a personal level to help individuals see that they can make a difference in improving or saving lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 16 publications
1
48
0
Order By: Relevance
“…For example, area-level studies that examine the distribution and quality of care within CKD clinics, particularly those that serve racial-ethnic minority communities, may provide valuable insight on how (and whether) expansion of health insurance coverage might change access to high-quality predialysis care for racial-ethnic minority groups. Similarly, studies that incorporate social workers and financial counselors into LDKT educational efforts have reported early success in reducing patients’ financial concerns regarding the LDKT process (40). However, the impact of such interventions on subsequent progress through the LDKT process has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, area-level studies that examine the distribution and quality of care within CKD clinics, particularly those that serve racial-ethnic minority communities, may provide valuable insight on how (and whether) expansion of health insurance coverage might change access to high-quality predialysis care for racial-ethnic minority groups. Similarly, studies that incorporate social workers and financial counselors into LDKT educational efforts have reported early success in reducing patients’ financial concerns regarding the LDKT process (40). However, the impact of such interventions on subsequent progress through the LDKT process has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized that lack of education may hinder both patients and donors from pursuing live donation. Lunsford et al suggested that education was the best way to attract live donation and dispel myths associated with living donation (19). While a handful of educational programs have been reported, ranging from short instructional videos to an educational question and answer session with transplant staff, many patients still felt ill equipped to pursue live donation and ask others to consider donating (1, 20–22), and interventions of education alone have not been shown to be particularly effective at increasing live donor transplantation rates for participants.…”
Section: Discussionmentioning
confidence: 99%
“…Potential live donors, especially those who are Black, harbor concerns about their future health if they donate [1214]. Potential donors who are Black also reported concerns about the financial costs of donation [13, 15]. Other possible barriers, such as cultural beliefs or interpersonal interactions, have rarely been examined among Black donors.…”
Section: Introductionmentioning
confidence: 99%